Impact of Chimney‐draught Conditions on Combustion and Emission Behavior of a Wood‐burning Stove. Issue 3 (29th December 2020) - Endriss, Felix; Grammer, Peter; Russ, Michael; Thorwarth, Harald
Abstract: Pollutants from combustion in wood‐burning stoves are influenced by many factors, including the exhaust gas system. This is responsible for the air supply due to the draught generated. Contrary to results reported in literature the experiments in this study show no effect on temperature related to increasing air supply and a total dust decreasing at higher draughts. The results also show no significant impact of the draught on gaseous emissions (CO/OGC/NOx ). The most significant loss was determined at thermal efficiency, which lost up to 13 % absolute with increasing draught. Abstract : Emissions from wood‐burning stoves are affected by several factors, including the chimney. This is responsible for the air supply and therefore decisive for the combustion conditions in a given stove. This study the effects of different draught conditions on the combustion, pollutants and thermal efficiency in a wood‐burning stove are investigated.